A model to assess students' social responsibility behavior within a classroom experiment. (January 2015) - Rodrigo-González, Amalia; Caballer-Tarazona, María
Abstract: This work proposes a teaching–learning activity encouraging students to reflect on and discuss a range of social values such as respect, solidarity, and social justice. The main goal is to assess students' social responsibility behavior and encourage reflection within the proposed activity. To this purpose, we design an experimental activity carried out in the classroom in order to create interest and raise awareness amongst students on issues related to social responsibility with economic value. Finally, we use data generated in this experiment to estimate a model based onFehr and Schmidt (1999), who explain how emotions affect individuals' decision making processes.